2023
DOI: 10.1111/rec.14023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Spartina alterniflora eradication on waterbirds and benthic organisms

Chenxue Lyu,
Shen Zhang,
Xiaotong Ren
et al.

Abstract: There has been an increasing number of coastal restoration projects to eradicate Smooth cordgrass (Spartina alterniflora) and restore bare tidal flats to conserve waterbirds. However, the evidence for the assumed benefits to waterbirds and benthic organisms after such restoration efforts remains limited. We evaluated the impact of S. alterniflora eradication on waterbirds and benthic organisms in southern China. We deployed time‐lapse cameras and satellite trackers to quantify and compare the occurrence freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…(P11): In a study examining the role of invasive grass Spartina alterniflora in the functioning of mud flat ecosystem in China, Lyu et al (2023) demonstrated that mud flats freed of invasive Spartina grass attracted almost all local waterbirds that had previously avoided the Spartina-infested area. Spartina can reach 1.5 m in height and create a significant barrier to forage for the waterbirds, findings, more research is needed to understand what seagrass shoot density is optimal for varying light conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(P11): In a study examining the role of invasive grass Spartina alterniflora in the functioning of mud flat ecosystem in China, Lyu et al (2023) demonstrated that mud flats freed of invasive Spartina grass attracted almost all local waterbirds that had previously avoided the Spartina-infested area. Spartina can reach 1.5 m in height and create a significant barrier to forage for the waterbirds, findings, more research is needed to understand what seagrass shoot density is optimal for varying light conditions.…”
Section: Introductionmentioning
confidence: 99%